Multifractal analysis and modification of coal pore structures with impact of clean compound biomass surfactants - Yang, Lingling; Yuan, Yuan (Frontiers in Physics, 2025)
This study investigates the modification of coal pore structures using composite biomass surfactants and explores its implications for methane adsorption and desorption characteristics. Coal samples from the 13–1 coal seam in Liuzhuang Mine, Huainan, China, are analyzed using low-temperature nitrogen adsorption experiments. The box-counting-based multifractal theory is used to assess coal pore heterogeneity and connectivity before and after surfactant treatment. The results reveal significant improvements in pore structure uniformity and connectivity, providing insights into the relationship between pore characteristics and methane adsorption behavior. This research offers a foundational understanding for optimizing coalbed methane extraction and enhancing environmental sustainability in coal mining operations.